2014
DOI: 10.5539/ass.v10n7p221
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Child-Centered Play Therapy Training in Malaysia

Abstract: Play therapy in Malaysia is still in the early stages of development. This study investigated the effectiveness of Child-Centered Play Therapy by conducting 3-day training sessions in different part of Malaysia for a total of 116 participants including mental health students and practitioners. Four research questions guided this study in exploring the differences on the three subscales: attitude, knowledge, and skills in play therapy. A repeated measure design was used for the pre-test and post-test instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Only a few studies have been published on brief forms of filial therapy, which are often provided as a means of delivering training in situations that may not allow for a full 10-week course of CPRT or CTRT. Several international studies have found that brief forms of intensive play therapy training offered effective results for rural communities that had not previously had access to professional level CCPT services (Cooper & Oliaro, 2019; Hunt, 2010; Johari et al, 2014; Wicks et al, 2018). Cooper and Oliaro (2019) developed and utilized a SBFT program for teachers and paraprofessionals in rural communities in Australia to learn CCPT skills over a 3-day period.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies have been published on brief forms of filial therapy, which are often provided as a means of delivering training in situations that may not allow for a full 10-week course of CPRT or CTRT. Several international studies have found that brief forms of intensive play therapy training offered effective results for rural communities that had not previously had access to professional level CCPT services (Cooper & Oliaro, 2019; Hunt, 2010; Johari et al, 2014; Wicks et al, 2018). Cooper and Oliaro (2019) developed and utilized a SBFT program for teachers and paraprofessionals in rural communities in Australia to learn CCPT skills over a 3-day period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We consider the intervention we conducted to be brief CTRT, as we utilized the 2020 CTRT Treatment Manual . Some brief trainings in school-based CCPT/ SBFT have been offered to school counselors, teachers, and paraprofessionals in hopes of maximizing the reach of effective play therapy in school settings (Cooper & Oliaro, 2019;Johari et al, 2014;Kagan & Landreth, 2009;Lindo et al, 2014;Pereira & Smith-Adcock, 2013). Only a few studies have been published on brief forms of filial therapy, which are often provided as a means of delivering training in situations that may not allow for a full 10-week course of CPRT or CTRT.…”
Section: Brief Filial Therapy Trainingmentioning
confidence: 99%
“…Although this expressive art therapy is still in its development in Malaysia, it is gaining popularity (Johari et al, 2014;Sakari, 2020). This type of therapy is also in line with current trends, especially when it comes to high-risk groups, such as delinquent adolescents.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Intuition in Depression by Remmers & Michalak (2016) also showed the importance of adolescents who are free from depression, anxiety and high stress will indicate good and prosperous psychological development. Furthermore, the use of expressive art therapy lessens the difficulty for delinquent adolescents to translate their experiences because expressive art elements can satisfy their natural instincts, making this group socially and emotionally prosperous (Johari et al, 2014).…”
Section: Literature Overviewmentioning
confidence: 99%
“…Kagan and Landreth (2009) implemented a 2-day play therapy training for school counselors and teachers in northern Israel and found that short-term training had a significant impact on the school counselors’ and teachers’ knowledge of CCPT, but it did not change their attitudes about CCPT. Whereas 2 days produced mixed results in countries outside the United States (Kagan et al, 2009), short-term training between 3 and 6 days have been found helpful in other countries such as Kenya, Malaysia, and Tanzania (Hunt, 2006; Hunt, 2010; Johari, Bruce, & Amat, 2014). Responders to a survey of play therapists’ views on training and practice in the field of play therapy reported a variety of play therapy training experiences, with the majority of those happening at workshops.…”
Section: Play Therapy Training For Mental Health Professionalsmentioning
confidence: 99%